2017
DOI: 10.1016/j.exphem.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Murine hemogenic endothelial precursors display heterogeneous hematopoietic potential ex vivo

Abstract: Hematopoietic Stem and Progenitor Cells (HSPCs) sustain life-long hematopoiesis and are first detected in the embryo by transplantation at embryonic day 10.5. (E10.5). HSPCs are mesodermal in origin and ultimately emerge from a subset of arterial endothelium (i.e. hemogenic endothelium), which is highly concentrated in the aorta-gonad-mesonephros region (AGM) of the mid-gestation embryo. Here, we employ clonal ex vivo assays in which endothelial cells isolated from the mid-gestation aorta and vitelline and umb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…This indicates that only a limited number of EC in the PE are able to transform into cells having hemogenic potential. Such observation is consistent with quantitative evaluations, performed by other authors, for the HE found in various locations (Ganuza et al 2017). Our detecting of CD31/Runx1-double-positive cells may suggest the presence of the HE in the PE.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This indicates that only a limited number of EC in the PE are able to transform into cells having hemogenic potential. Such observation is consistent with quantitative evaluations, performed by other authors, for the HE found in various locations (Ganuza et al 2017). Our detecting of CD31/Runx1-double-positive cells may suggest the presence of the HE in the PE.…”
Section: Discussionsupporting
confidence: 93%
“…The variability of colonies grown from specific-cell-type populations isolated from the PE in our study may reflect the HE heterogeneity, which had been suggested by other authors (Ganuza et al 2017). …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“… 34 Clonal output is also likely heterogenous, as recent work using limited dilutional analyses suggests, with increased heterogeneous HSPC populations at E10 vs. E11. 42 Thus, IAHC formation is likely driven by the rapid cell proliferation of several hemogenic endothelial clones with differing functional capacities. These findings further support a recent observation that an initial pool of pre-HSCs is established, from which HSCs mature from by E11.5.…”
Section: Discussionmentioning
confidence: 99%
“…This research collectively indicated that the appearance of cells having definitive HSC characteristics is in close association with arterial endothelium. Notably, umbilical arteries have been identified by a number of investigators as one of the primary birthplace of HSCs except the dorsal aorta in the aorta-gonad-mesonephros (AGM) region and the vitelline arteries [13,14], raising the possibility that arterial endothelial cells (AECs) within umbilical cord might harbor a complex network of signals to modulate the nascent HSCs. Interestingly, there is growing evidence that endothelium not only plays a fundamental role in the generation of definitive HSCs but also is essential for the self-renewal of HSCs in vitro or BM repopulation in vivo recently [15,16].…”
Section: Introductionmentioning
confidence: 99%